Change and continuity: caring for children and young people - Carole Wilkinson (Scottish Journal of Residential Child Care)
The article is the author's reflections on a working life in social care that has spanned over 20 years in Scotland, starting with the most recent as Chair of Scottish Children's Reporter Administration. It examines changes since the Killbrandon report, arguing that change has not fundamentally altered the original philosophy and has helped bring the Hearing System into the 21st century. Some of the changes have been about ensuring children, young people and their families can participate more fully in their Panel Hearings. It then goes on to highlight some of the work now in progress to further the aim of better hearings for all those involved. The article then looks back at the establishment of the Scottish Social Services Council and the registration and regulation of the social services workforce, covering some of the debates and arguments. It examines issues around the status of the workforce particularly residential child care staff, and what still needs to be done to achieve proper recognition for such a demanding and important role.